Jugular foramen schwannoma: A rare tumor treated by stereotactic radiosurgery - Bansal, Manishi; Jindal, Ankush; Jindal, Anupam; Das P, Mohan (Indian Journal of Case Reports, 2022)
Jugular foramen schwannomas (JFS) are rare benign tumors located in the jugular foramen. They can present with various symptoms depending on the extent of involvement of the tumor such as hearing loss, tinnitus, headache, and ataxia. Surgical resection has been considered as the primary treatment option for JFS. Stereotactic radiosurgery (SRS) offers an equally good treatment in patients with small and residual tumors after surgery with the advantage of being non-invasive with minimal complication rates. Herein, we present a rare case of JFS treated by SRS in our institution.